Analisis Semiotika Pada Kumpulan Puisi “Dari Aku Yang Hampir Menyerah” Karya Khoirul Trian - Sari, Ana; Kasmantoni, Kasmantoni; Andra, Vebbi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the denotative and connotative meanings in several poems that highlight themes of life's struggles, sadness, and hope, while understanding the messages contained within these poems through the perspectives of two language experts, Mr. Alfian and Ms. Yuli. The research method used is qualitative interviews with two language professors who interpret the poems based on their denotative and connotative meanings, along with an analysis of five poems that depict emotional experiences and challenges in life. The research results indicate that each poem contains profound and complex meanings, with themes of resilience, loneliness, and hope; both experts agree that these poems imply the importance of introspection, emotional support, and acceptance of life’s circumstances, highlighting that despite facing difficulties, individuals still have the ability to rise and continue living with optimism. Conclusion, poetry serves not only as a form of artistic expression but also as a powerful medium for conveying life messages, with a message emphasizing the importance of self-care, accepting support, and maintaining optimism even in challenging times. Additionally, understanding denotative and connotative meanings helps readers delve deeper into the human experiences represented in poetry. Keywords: Emotional Support, Denotative Meaning, Connotative Meaning, Life's Struggles, Poetry, Interviews.